Analisis Faktor-Faktor Yang Mempengaruhi Implementasi Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (Sak Etap) Pada Usaha Mikro Kecil Dan Menengah (Studi Kasus Pengrajin Mebel di Desa Rau Kecamatan Kedung Kabupaten Jepara) - Nevi Selfiana Safitri; Ichwan Marisan (Accounting Study Program, Faculty of Economics and Business, 2021)
Micro, small and medium enterprises are an economic activity that is established and managed by a part or group of people who are small in nature but greatly affect the national economy. The purpose of this study was to determine the effect of the owner's education level, information and socialization of SAK ETAP, business size and age of business on the implementation of SAK ETAP on MSME furniture craftsmen in Rau village. This study uses a quantitative approach using primary data. The population in this study were MSME furniture craftsmen in Rau village, which amounted to 55 MSMEs. In this study, there are four variables, namely the owner's education level, information and socialization of SAK ETAP, business size and age of business as independent variables and implementation of SAK ETAP as the dependent variable. The results of this study indicate that the owner's education level, information and socialization of SAK ETAP variables and business size have a positive effect on the implementation of SAK ETAP. While the variable age of business has no effect on the implementation of SAK ETAP.